Assessing the health implications of anticholinergic drugs in older people - Mariangela Boccardi; Virginia Boccardi (Geriatric Care)
In this narrative review, we analyzed the existing literature on the pros and cons of anticholinergic medications, focusing on their prevalence, underlying mechanisms, and methods of assessment. Our review underscores the significant adverse effects of anticholinergic drugs, particularly on cognition and functional abilities in older adults. These effects include the exacerbation of various cognitive states, increased psychiatric symptoms, heightened risk of delirium, functional decline, elevated hospitalization rates, greater likelihood of institutionalization, and increased mortality. While anticholinergic medications provide therapeutic benefits, their use in older adults requires careful evaluation due to these considerable risks. Discontinuation of anticholinergic therapy offers both benefits and challenges. We propose practical guidelines for their use in clinical contexts such as dementia, schizophrenia, depression, anxiety, Parkinson’s disease, cardiovascular conditions, and urinary incontinence.